A descriptive analysis of e-Commerce strategies - Cordero, Camille Andrea Zarate (College of Home Economics, University of the Philippines, 2009)
This thesis is a pilot study on e-commerce on Multiply. The general objective of this study was to describe the e-commerce strategies employed for apparel online stores. This study specifically aimed to classify the customer interface design elements, to analyze the relationships between the customer interface design elements and its connection to the value proposition of the online store and to determine the e-commerce strategies utilized by the apparel online stores. Purposive sampling was used in selecting the five apparel online stores. The criteria primarily focused on Philippine apparel online stores and the female apparel market. Qualitative research through descriptive content analysis of the interface of the website was used. Profiles of the five apparel online stores were utilized to describe the value propositions and product offerings of the websites. Ocular observation and navigation of the website were done to gather the needed information details for the survey checklist. The survey checklist determined the map frameworks which identified the classification of each customer interface design element. The researcher described the implementation of e-commerce strategies by relating the design element to the corresponding e-commerce strategies. The study showed that there are seven customer interface design elements in the e-commerce website on Multiply.These seven customer interface design elements are context, content, community, connection, communication, customization and commerce. Based on the map framework, content, context and connection significantly depend on the value proposition and product offering. Community, commerce, communication and customization do not greatly differ in the classifications of the design elements. The strategies were divided into six: promotion of the website, design of the website, creation of the electronic catalogue, method of order processing, preference of security systems and customer support and interaction. E-commerce on Multiply is continuing gaining popularity. Apparel online stores are developing strategies in order to compete. Further studies of this research can be the evaluation of the website's strategies effectiveness used in the website. On the business aspect, a case study of the online stores to see if Multiply is an effective platform for entrepreneurs.